2020
DOI: 10.3390/nano10020286
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Citral and Pompia Essential Oil Loaded in Phospholipid Vesicles for the Treatment of Skin and Mucosal Infections

Abstract: Citrus species extracts are well known sources of bio-functional compounds with health-promoting effects. In particular, essential oils are known for their antibacterial activity due to the high content of terpenes. In this work, the steam-distilled essential oil from the leaves of Citrus limon var. pompia was loaded in phospholipid vesicles. The physico-chemical characteristics of the essential oil loaded vesicles were compared with those of vesicles that were loaded with citral, which is one of the most abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…In light of this, essential oils may represent a valid alternative to avoid the multidrug resistance of many pathogens, or they could be used in combination with antimicrobials to improve their effectiveness against different infectious diseases 65 . In addition, several studies have suggested that their delivery into ad hoc formulated carriers may improve their efficacy 66 .…”
Section: Resultsmentioning
confidence: 99%
“…In light of this, essential oils may represent a valid alternative to avoid the multidrug resistance of many pathogens, or they could be used in combination with antimicrobials to improve their effectiveness against different infectious diseases 65 . In addition, several studies have suggested that their delivery into ad hoc formulated carriers may improve their efficacy 66 .…”
Section: Resultsmentioning
confidence: 99%
“…Liposomes increase drug half-life, improve the therapeutic index, and are considered biocompatible and biodegradable [ 29 , 30 ]. It has been also described that liposomes can enhance the activity of natural compounds, such as citral and thymus essential oils, which improve their antifungal and antioxidant activity, respectively, when formulated in liposomes [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…As recently reported by Usach and coworkers, pompia essential oil (containing limonene and citral) as well as citral itself were successfully loaded into liposomes via hydration followed by ultrasonic disintegration. The respective encapsulated terpenoids had antimicrobial properties against different bacterial species such as S. aureus or P. aeruginosa [18]. A nanoemulsion comprising eucalyptus oil obtained by ultrasonic emulsification was also shown to have antibacterial activity against S. aureus [19].…”
Section: Introductionmentioning
confidence: 98%
“…In addition to nanostructured lipid carriers, terpenoids can also be delivered by encapsulation into polymeric nanostructured systems or by molecular complexation [2]. In addition to increasing stability of encapsulated compounds, terpenoid-encapsulation systems are widely accepted to be non-cytotoxic and enhance the antioxidant and anti-inflammatory activities of terpenoids ( [18,[21][22][23] reviewed in [2,24]). For instance, Manconi and colleagues reported the liposomal formulation of thymus essential oil to be highly biocompatible and to counteract oxidative stress in keratinocytes [22].…”
Section: Introductionmentioning
confidence: 99%